PSYCHOLOGICAL DETERMINANTS OF ATHLETIC PERFORMANCE IN FEMALE SOFTBALL PLAYERS: THE ROLE OF MENTAL TOUGHNESS, COMPETITIVE ANXIETY, AND GOAL ORIENTATION - Shapri, Jessyla @ Assad; Wazir, Mohd Rozilee Wazir Norjali; Nazarudin, Mohamad Nizam (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
This study examines the psychological determinants of athletic performance in female softball players, focusing on mental toughness, competitive anxiety, and goal orientation. We conducted a quantitative cross-sectional survey of 120 participants from the Sabah Schools Sports Council Softball Championship, using validated instruments: the Sport Mental Toughness Questionnaire (SMTQ), the Competitive State Anxiety Inventory-2 (CSAI-2), and the Task and Ego Orientation in Sport Questionnaire (TEOSQ). Descriptive analysis revealed that constancy, a component of mental toughness, was the highest-scoring factor, while cognitive anxiety emerged as the most prevalent form of competitive anxiety. Task orientation dominated goal orientation, particularly among high-achieving athletes. MANOVA results indicated significant differences in psychological constructs across achievement levels and age groups; champion teams exhibited higher confidence and control, whereas runner-up teams reported elevated somatic anxiety. Moreover, older athletes demonstrated stronger self-confidence and ego orientation. The findings underscore the critical influence of psychological factors on performance outcomes, suggesting that mental toughness and task-oriented motivation are key predictors of success. This research contributes to the growing body of literature in sport psychology by empirically validating the interplay between these constructs among competitive female athletes. The results have practical implications for designing targeted mental training interventions to optimize athletic performance.